In vitro biosynthesis of diphthamide, studied with mutant Chinese hamster ovary cells resistant to diphtheria toxin. - Moehring, T J (1984)
Diphthamide, a unique amino acid, is a post-translational derivative of histidine that exists in protein synthesis elongation factor 2 at the site of diphtheria toxin-catalyzed ADP-ribosylation of elongation factor 2. We investigated steps in the biosynthesis of diphthamide with mutants of Chinese hamster ovary cells that were altered in different steps of this complex post-translational modification. Biochemical evidence indicates that this modification requires a minimum of three steps, two of which we accomplished in vitro. We identified a methyltransferase activity that transfers methyl groups from S-adenosyl methionine to an unmethylated form of diphthine (the deamidated form of diphthamide), and we tentatively identified an ATP-dependent synthetase activity involved in the biosynthesis of diphthamide from diphthine. Our results are in accord with the proposed structure of diphthamide (B. G. VanNess, et al., J. Biol. Chem. 255:10710-10716, 1980).